Adolescent psychology - Muxammadieva X (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article describes the processes of the transition to adolescence in students. Sudden changes in adolescent development. These changes are physiological and psychological changes. Physiological change is the beginning of puberty and, in connection with this, the perfect development and growth of all cells in the body, the re-formation of cell and body structures is revealed